A study on the causes of the inconsistencies of the microstructure of welded joints of steel wire cord - I. V. Borisovets; T. P. Kurenkova; A. A. Sakharnaya (Литьë и металлургия, 2019)
Relevance: the increase in the number of destruction of welded joints of the metal wire cord due to discrepancies in the microstructure of the welded seam.Purpose: to find the roots of defects in welded joints of metal wire cord to reduce the number of inconsistencies in this parameter and study the features of the formation of the microstructure of welded joints.Methods of research: as a material for research the metal wire cord of various designs made in steel – wire shop No. 2 of OJSC «BSW – Management Company of Holding «BMC» – a rod of own production was applied; the study was conducted using a Nikon SMZ 1000 stereoscopic microscope with a video system and an inverted metallographic microscope OLIMPUS GX-51 with a video system; measurement of hardness was carried out according to Vickers with a load of 0.5 kg on a hardness testing ZWICK 3Х5624АТ.Research results: the regularities and causes of the formation of mismatch of the microstructure of welded joints during welding on metal: incorrect setting of the welding machine (slowing down of the welding carriage); mismatch of the tempering temperature (a faulty button or operation home run twice); a small dwell time in the terminals (jaws) for tempering; inadequate execution of Regulation of the welded connection of the operator’s actions (pass or failure of the operation «tempering of the weld»); influence of external environmental factors (microclimate) of the operator’s workplace.